KONTRIBUSI PEREMPUAN PEDAGANG SAYURAN TERHADAP PENDAPATAN KELUARGA DI PASAR BAHU MANADO - Yulistien ., Djangaopa; Elsje Pauline Manginsela; Jenny ., Baroleh (Sam Ratulangi University, 2018)
The objectives of the research are: to find out (1) the contribution of income from trading vegetables to family income and (2) the outpouring of working hours of green vegetable traders at the Manado Bahu Market. This study used primary and secondary data. Primary data is colected through direct interviews with respondents based on the questionnaire. Secondary data were obtained from the relevant agencies, namely the Market Service Office Manado City and Sub-Office of Manado Bahu Market and literature review relating to the research topic, namely the Contribution of Women to Vegetable Traders as Family Income and the daily time spent. The sampling method used purposive sampling method which was limited to women who had ever married who sold green vegetables including kale, spinach, and gedi. The number of respondents was 15 women sellers of green vegetables. The results of the study showed that the average contribution of income per month from green vegetable traders to household income was 58.56% or Rp. 3,345,333. The average amount of time spent in a day to take care of the household is 5.33 hours per day with a percentage of 22.21%, while the average time spent by women vegetable traders in Manado Bahu Market is 6.73 hours per day with a percentage of 28.04% and time for other activities, including social activities and resting, an average of 11.93 hours per day with a percentage of 49.70%.*eprm*.